1979
DOI: 10.1111/j.1365-2125.1979.tb04690.x
|View full text |Cite
|
Sign up to set email alerts
|

Diuretics, beta‐blockers or both as treatment for essential hypertension.

Abstract: 1 Patients with borderline (group I) and sustained hypertension (group II) were treated with 3-blocking drugs, diuretics and the combination of both. In the two groups of patients the antihypertensive effectiveness of both short-term intravenous or chronically oral propranolol was directly related to the extent to which the drug produced an absolute reduction in plasma renin activity (PRA). No such a correlation could be obtained with pindolol. In group I following ,B-blockade, day-night profiles of PRA were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…However, the target was reached in only 50% of those aged 4 0 -6 0 years, and in a mere 20% of patients above the age of 60 years. The predictive value of age has also been confirmed by others (31,32). Due to the fact that older patients and those with a low renin respond better to diuretics than to /3-blocker monotherapy adds complementary confirmation to the concept of a treatment strategy based on age and renin (33)(34)(35).…”
Section: Renin Prognosticates Antihypertensive Responsesupporting
confidence: 49%
“…However, the target was reached in only 50% of those aged 4 0 -6 0 years, and in a mere 20% of patients above the age of 60 years. The predictive value of age has also been confirmed by others (31,32). Due to the fact that older patients and those with a low renin respond better to diuretics than to /3-blocker monotherapy adds complementary confirmation to the concept of a treatment strategy based on age and renin (33)(34)(35).…”
Section: Renin Prognosticates Antihypertensive Responsesupporting
confidence: 49%
“…Two aspects are of particular interest. Firstly, the degree of antihypertensive activity seems greater than might be anticipated from previous reports of the effects of diuretics (Stumpe & Overlack, 1979;Freis, 1960), and is more in keeping with the reported effects of f3-adrenoceptor blocking agents ). Xipamide appears to exercise control throughout the whole day including the hours of rapid rise between 05.00 h and 10.00 h. Both of these facts may be of considerable clinical importance .…”
Section: Discussionmentioning
confidence: 52%
“…Heterogeneity of BP response to different antihypertensive agents is well-known among clinicians [48]. It was first recognized when earlier studies with diuretics and β-blockers reported a differential response to these drugs among hypertensive people [49][50][51][52]. Such variability of response was later con-Review firmed also with other antihypertensive drug classes, such as ACEi and calcium channel blockers (CCBs) [53][54][55][56][57][58][59].…”
Section: Variability Of Response To Different Anti-hypertensive Drug mentioning
confidence: 99%